Immune response to SARS-CoV-2 infection and vaccination in patients receiving kidney replacement therapy - Ikizler, T. Alp (Kidney Int, 2021)
In this issue of Kidney International, the initial experience regarding the immunogenicity of prior coronavirus disease 2019 (COVID-19) infection and the response to the COVID-19 vaccines among patients on maintenance dialysis and kidney transplant recipients is summarized. Preliminary data suggest that there is durability of immune response after COVID-19 infection. Although immune response to the first dose of vaccine is less in infection-naïve patients than healthy individuals in both groups, after the second vaccine dose a significant portion of patients receiving maintenance dialysis develop robust antibody titers, whereas kidney transplant recipients show a less-strong immune response.